Efficacy and safety of Xingnaojing injection for post-operative patients of intracerebral haemorrhage: a meta-analysis and systematic review - Song, Yanbo; Xu, Fangbiao; Li, Shuliang; Sun, Yongkang; Wang, Xinzhi (Frontiers in Pharmacology, 2024)
Background: Intracerebral haemorrhage (ICH) is the deadliest subtype of stroke. Surgery remains a vital measure for life-saving in emergency situations, however, the recovery of post-operative patients is not optimistic. This study aimed to evaluate the evidence of the efficacy and safety of Xingnaojing injection (XNJ) for post-operative patients of ICH. Method: From inception to January 31, 2024, we searched 8 representative databases for randomized controlled trials on post-operative patients of ICH treated with XNJ. A meta-analysis was conducted using R4.2.2, and the quality of the evidence was evaluated by GRADE criteria. Result: The results indicated that the combination of XNJ with conventional western medicine therapy improved the total efficiency rate (RR = 1.26; 95% CI [1.21 to 1.32]; p < 0.0001), reduced the all-cause mortality within 15 days (RR = 0.45; 95% CI [0.30 to 0.67]; p < 0.0001), decreased the volume of hematoma (MD = -4.72; 95% CI [-7.43 to -2.01]; p = 0.0006) and perihematomal edema (MD = -4.11; 95% CI [-8.11 to -0.11]; p = 0.0441), reduced the TNF-α levels (SMD = -1.61, 95% CI = (-2.23, -0.99), p < 0.0001), decreased neurological impairment (SMD = -1.44; 95% CI [-1.78 to -1.11]; p < 0.0001), improved the activities of daily living (SMD = 1.22; 95% CI (0.78 to 1.66]; p < 0.0001), and enhanced the consciousness level (MD = 2.08, 95% CI [1.22 to 2.93), p < 0.0001). In addition, the complications of the combination therapy group were lower (RR = 0.43; 95% CI [0.35 to 0.54]; p < 0.0001) and the adverse drug reactions were comparable to the control group (RR = 0.89; 95% CI [0.55 to 1.45]; p = 0.6521). The trial sequential analysis results showed that the sample size is sufficient. Conclusion: Current evidence indicates that XNJ can enhance the efficiency, reduce mortality, and lower the incidence of complications, while demonstrating good tolerability of post-operative patients of ICH. However, the level of evidence from existing studies is relatively weak, and only prove short-term effects, and high-quality RCTs are needed to further verify the accuracy of these conclusions.